Pemanfaatan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi di Sekolah Dasar - Prasanti, Nissa; Sofiyanurriyanti, Sofiyanurriyanti; Hidjrawan, Yusi; Marlinda, Marlinda; Hartati, Rita; Kasmawati, Kasmawati; Irmayani, Irmayani; Basuki, Mahmud; Akmal, Abdiel Khaleil (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The implementation of this training was themed Utilization of Information and Communication Technology-Based Learning Media in Elementary Schools. The purpose of this training is to increase students' awareness of the importance of information and communication technology-based learning media in elementary schools. The training participants were students of SDN Ujong Patihah. The training participants took part in socialization in the form of lectures, discussions, and questions and answers regarding technology-based learning media. The output of this training is to open students' insights as the younger generation who live in the millennial era and in facing the industrial revolution 4.0, it is hoped that this will further improve technology-based learning media. In addition, the younger generation must also have qualified skills or abilities so that they can easily adapt to various technological developments, and not be increasingly left behind and lost in local and global competition. Technological developments have made it easier for the younger generation to learn both online and offline.